(3cJGH GdNhGUs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3ceGd Hf XgjQ GdOjf Hf GNJjGQ GdOjf eMeO GdeJWHH s)
(3ChdgG (B:s
(3bGd CHh HcQ , eMeO Hf RcQjGA GdQGRi (B: (3Efi dG CYde Cf bhekG eef TGbge GdWYf hGdhGbYjI hGdJSQY s
(3BNQgG (B:s
(3heKd gPG ai WHGY GdCTLGQ hGdMjhGf hGdeYGOf eeG bOQCjfGg hTGgOfGg cKjQkG hgh YdGe GdZjhH s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B79 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs